KONTRIBUSI VO2 MAX, POWER TUNGKAI DAN KOORDINASI MATA TANGAN TERHADAP KETERAMPILAN BERMAIN BOLAVOLI PADA ATLET BOLAVOLI KABUPATEN BULUKUMBA - Marsan, Riswan Aksaril (Program Studi Pendidikan Jasmani Kesehatan dan Rekreasi STKIP Mega Rezky Makassar, 2017)
The study aims at examining (1) whether there is contribution of VO2 max towards volleyball skills of the athletes in Bulukumba, (2) whether there is contribution of leg power towards volleyball skills of the athletes in Bulukumba, (3) whether there is contribution of hand-eye coordination towards volleyball skills of the athletes in Bulukumba, (4) whether there is contribution of VO2 max, leg power and hand-eye coordination towards volleyball skills of the athletes in Bulukumba district. The study is descriptive research. The population is the volleyball athletes in Bulukumba with the total of 50 people, selected by employing purposive sampling technique. Data is analyzed using correlation analysis technique assisted with SPSS computer program at the significant level 95% or α=0.05. The results of the study reveal that (1) there is contribution of VO2 max towards volleyball skills of the athletes in Bulukumba by 48.50%; whereas, 51.50% is caused by other factors whichare not explained in this study, (2) there is contribution of leg power towards volleyball skills of the athletes in Bulukumba by 59.50%; whereas, 40.50% is caused by other factors which are not explained in the study, (3) there is contribution of hand-eye coordination towards volleyball skills of the athletes in Bulukumba by 43.20%; whereas 56.80 is caused by other factors which are not explained in this study, and (4) there is contribution of VO2 max, leg power, and hand-eye coordination toward volleyball skills of the athletes in Bulukumba district by 66.00%; whereas, 34% is caused by other factors which are not explained in this study.